Research on Public Opinion Guidance and Governance Strategy of Social Media Platform - Fu Xinyi (SHS Web of Conferences)
With the rapid development of Internet technology, social media platforms have risen rapidly and become an indispensable part of people’s daily lives. It greatly facilitates access to information, with fast dissemination speed, wide coverage, and many participants. However, its openness and freedom have also led to many problems, such as spreading false information, online violence, privacy breaches, etc., seriously disrupting the healthy online public opinion environment and threatening social stability and national security. The government and relevant institutions should strengthen the supervision of social media platforms, formulate clear laws and regulations, and crack down on illegal activities such as spreading false information and infringing on privacy. Social media platforms should also take responsibility, improve platform rules, strengthen the published content review mechanism, and avoid spreading harmful information. Strengthening public online literacy education is an important aspect that cannot be ignored in guiding healthy public opinion and creating a good online environment. We can fundamentally purify cyberspace by improving the public's identification ability and enhancing self-protection awareness.